Envenomation by Dangerous Jellyfish in Indonesia and Adjacent Areas: A Literature Review - Manafe, Carolian Janicca Winda; Zirly Vera Aziri (Jurnal Biologi Tropis, 2024)
This article reviews the epidemiology, etiology, pathogenesis, clinical manifestations, diagnosis, management, prognosis, and complications associated with jellyfish stings. Cases of jellyfish envenomation are increasing in line with climate change and human activities in aquatic environments. Data show that jellyfish envenomation is frequent in tropical and subtropical waters, with the number of cases reported in Australia and the Western Pacific region, as well as some cases in Indonesia is higher compared to rest of Asia. The jellyfish species Chironex fleckeri, Portuguese man o' war, and Carukia barnesi have the potential to cause severe and life-threatening systemic manifestations. The initial management of jellyfish stings remains uncertain and is still a subject of debate. Appropriate and prompt first aid is crucial for improving the patient’s prognosis. Other factors, such as the patient's condition and the environment, also affect prognosis and the potential for complications.